The Damages of Medical Records in the Outpatient Room in Dr. R. Soeharsono Lv.III Hospital Banjarmasin - Septy Handayani; Arief Budiman; Rabiatul Adawiah (Formosa Journal of Sustainable Research, 2022)
Medical records function to record and store identity, diagnose, treatment, and services history provided to patients in the health facilities. This study aims to determine the factors that cause damage to medical records in the outpatient room at Dr. R. Soeharsono Lv.III Hospital, Banjarmasin. This is descriptive research with data derived from observations, interviews, and measurements. The results showed that the highest incidence of document damage in the 2019 was 24 files. Lighting conditions ranged from 40-99 lux. The temperature in the medical record room is 18⁰ C -28⁰ C and the fire extinguisher is placed outside the filing room. In the medical record room, there are 2 damp documents. The presence of nuisance insects was not found and there were officer activities such as eating or drinking in the room. There were 2 medical record documents that had faded in the patient's name